The political role of the media in the democratisation of Malawi : the case of the Weekend Nation from 2002 to 2012 - Gunde, Anthony Mavuto (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015